Improved discharge energy density and efficiency of polypropylene-based dielectric nanocomposites utilizing BaTiO3@TiO2 nanoparticles. (December 2022) - Xie, Haoran; Luo, Hang; Pei, Zhantao; Chen, Sheng; Zhang, Dou
Abstract: With increased requirements from the miniaturization, lightweight and integration of electronic devices, it is urgent to improve the discharge energy density ( U e ) of commercial polypropylene (PP) film capacitor. In this work, core-shell structure BaTiO3 @TiO2 nanoparticles were introduced into polypropylene matrix via melt mixing method. Due to the existence of the transition layer, the addition of BaTiO3 @TiO2 nanoparticles can increase the interfacial polarization of the composites without causing obvious local electric field concentration in comparison with bare BaTiO3 nanoparticles. Moreover, BaTiO3 @TiO2 nanoparticles can act as an electron trap to inhibit the movement of carriers and hinder the growth of the electrical tree, thereby promoting the breakdown strength ( E b ) of PP-based nanocomposites. As a result, the U e of the nanocomposite with 6 wt% BaTiO3 @TiO2 nanoparticles was improved from 4.28 J/cm 3 of pure PP to 5.58 J/cm 3, maintaining a high efficiency of more than 95%. This study provides an effective strategy to optimize energy storage density of PP film capacitors. Graphical abstract: Image 1 Highlights: Core-shell BaTiO3 @TiO2 nanoparticles were prepared by a facile hydrolysis method. Gradient changes in ε r of fillers weakened local electric field concentration. The composite achieved an U e of 5.58 J/cm 3 and a high ƞ of over 95% at 580 kV/mm.